The Analysis of Internal Controls on Revenue and Expenditure Cycle in PT. Levina - Leonny Ariesa; Ruben Garcia Berasategu (Journal of Applied Finance & Accounting, 2009)
This research intends to observe and to examine the revenue and expenditure cycle implemented in PT. LEVINA as well to analyze, to assess, and to identify potential weaknesses in the revenue and expenditure cycle, and the internal controls related to those cycles of the company using COSO’s Internal Control-Integrated Framework. Moreover, it provides specific recommendations based on the framework to overcome the discovered potential weaknesses. The method of analysis used in this study is by assessing the current revenue and expenditure cycle implemented in the company, along with the internal controls applied within the cycles. Subsequently, the potential weaknesses will be identified which then generates the specific recommendations. The data-collection methods used are literature and field research. The current revenue and expenditure cycle of PT. LEVINA are still comprised with potential weaknesses such as structural weaknesses, documentation and business activities (procedures) weaknesses, and Internal Control (IC) weaknesses. Hence, as the company business keeps growing, it is important to focus more on its RC and EC system as well as the IC in order to achieve the most effective and efficient methods in operating the business. As the result, the company could become more profitable.